Promoter methylation patterns in Richter syndrome affect stem‐cell maintenance and cell cycle regulation and differ from de novo diffuse large B‐cell lymphoma. (21st August 2013) - Rinaldi, Andrea; Mensah, Afua Adjeiwaa; Kwee, Ivo; Forconi, Francesco; Orlandi, Ester M.; Lucioni, Marco; Gattei, Valter; Marasca, Roberto; Berger, Françoise; Cogliatti, Sergio; Cavalli, Franco; Zucca, Emanuele; et al.
Summary: In a fraction of patients, chronic lymphocytic leukaemia (CLL) can transform to Richter syndrome (RS), usually a diffuse large B–cell lymphoma (DLBCL). We studied genome‐wide promoter DNA methylation in RS and clonally related CLL‐phases of transformed patients, alongside de novo DLBCL (of non‐germinal centre B type), untransformed‐CLL and normal B‐cells. The greatest differences in global DNA methylation levels were observed between RS and DLBCL, indicating that these two diseases, although histologically similar, are epigenetically distinct. RS was more highly methylated for genes involved in cell cycle regulation. When RS was compared to the preceding CLL‐phase and with untransformed‐CLL, RS presented a higher degree of methylation for genes possessing the H3K27me3 mark and PRC2 targets, as well as for gene targets of TP53 and RB1. Comparison of the methylation levels of individual genes revealed that OSM, a stem cell regulatory gene, exhibited significantly higher methylation levels in RS compared to CLL‐phases. Its transcriptional repression by DNA methylation was confirmed by 5‐aza‐2′deoxycytidine treatment of DLBCL cells, determining an increased OSM expression. Our results showed that methylation patterns in RS are largely different from de novo DLBCL. Stem cell‐related genes and cell cycle regulation genes are targets of DNA methylation in RS.